Cats Parallel Great Apes and Corvids in Motor Self-Regulation – Not Brain but Material Size Matters - Bobrowicz, Katarzyna; Osvath, Mathias (Frontiers in Psychology, 2018)
The inhibition of unproductive motor movements is regarded as a fundamental cognitive mechanism. Recently it has been shown that species with large absolute brain size or high numbers of pallial neurons, like great apes and corvids, show the highest performance on a task purportedly measuring this mechanism: the cylinder task. In this task the subject must detour a perpendicularly oriented transparent cylinder to reach a reward through a side opening, instead of directly reaching for it and bumping into the front, which is regarded as an inhibitory failure. Here we test domestic cats, for the first time, and show that they can reach the same levels as great apes and corvids on this task, despite having much smaller brains. We tested subjects with apparatuses that varied in size (cylinder length and diameter) and material (glass or plastic), and found that subjects performed best on the large cylinders. As numbers of successes decreased significantly when the cylinders were smaller, we conducted additionally two experiments to discern which properties (length of the transparent surface, goal distance from the surface, size of the side opening) affects performance. We conclude that sensorimotor requirements, which differ between species, may have large impact on the results in such seemingly simple and apparently comparable tests. However, we also conclude that cats have comparably high levels of motor self-regulation, despite the differences between tests.